2010
DOI: 10.1016/j.nut.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhalational and oral supplementation of ascorbic acid may prevent influenza pandemic emergency: A hypothesis

Abstract: Occurrence of influenza pandemics is a worldwide phenomenon and a significant cause of mortality and morbidity throughout the globe. It is due to mutations in the influenza virus genetic material creating antigenic drift of pathogenic viral proteins resulting in emergence of new influenza virus strains. Therefore, the vaccines available for prevention of influenza offer no protection against influenza pandemics caused by new virus strains. Moreover, the existing drugs used to combat influenza may be ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…As this dose cannot be obtained from diet, oral vitamin C supplement might be recommended for people at risk of respiratory tract infection. It is hypothesised that a combined oral and inhalational vitamin C supplement maintain high level of vitamin C in bronchial epithelium and respiratory secretions which could have a protective antiviral effect against influenza virus [ 28 ]. Twenty-nine meta-analyses involving 11,077 participants showed that routine prophylaxis of high dose of vitamin C in normal population did not decrease the incidence of common cold [ 29 ].…”
Section: Antiviral Properties Of Vitamin Cmentioning
confidence: 99%
“…As this dose cannot be obtained from diet, oral vitamin C supplement might be recommended for people at risk of respiratory tract infection. It is hypothesised that a combined oral and inhalational vitamin C supplement maintain high level of vitamin C in bronchial epithelium and respiratory secretions which could have a protective antiviral effect against influenza virus [ 28 ]. Twenty-nine meta-analyses involving 11,077 participants showed that routine prophylaxis of high dose of vitamin C in normal population did not decrease the incidence of common cold [ 29 ].…”
Section: Antiviral Properties Of Vitamin Cmentioning
confidence: 99%
“…Pneumonia was reported in two subjects in the treatment group and 10 in the control group, and hospital stays for influenza or related complications averaged nine days in the vitamin C group and 12 days in the control group [81]. Therefore it has been considered that combined inhalation and oral supplementation of ascorbic acid may prevent influenza virus infection [82].…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…A high dose of vitamin C (12 g per day) significantly improved the condition of patients suffering from severe acute respiratory tract infections ( Kakodkar, Kaka, & Baig, 2020 ). Similarly, Banerjee and Kaul (2010) reported that the mega doses of vitamin C can be used to treat the common cold and flu in children. The administration of 15 g vitamin C per day decreased the mortality rate in the COVID-19 patients ( Carr, 2020 ).…”
Section: Nutrients Possessing Antiviral Propertiesmentioning
confidence: 99%